The Application of an Improved Fuzzy Comprehensive Evaluation in Coal Quality Rating: The Case Study of China - Cai, Feng; Yang, Lingling; Yuan, Yuan; Taghizadeh-Hesary, Farhad (Frontiers in Energy Research, 2022)
Coal quality rating can help reduce greenhouse gas emissions, solving the global warming problem. It becomes more important as the carbon neutrality by the mid-21st century agreement is accepted by 195 countries, including China. In this paper, an improved fuzzy comprehensive evaluation method is introduced for coal quality rating. The data used in this work are of the Hostolgoi coalfield of the Xinjiang Province of China. Six industrial analysis indicators are determined as evaluation factors by taking the coal samples of different coal seam depths in the mining area. The super-standard multiple methods and the double-weight super-standard weighting method are combined to form a comprehensive weight. The results show that most of the coal samples of this coal mine are at grades I–II, and the overall coal is with good-quality stability. The evaluation results can improve the coal utilization efficiency and provide scientific guidance for evaluating and exploiting coal resources in coal geological exploration.